An Examination of Ibn Khaldun's History and Islamic Political Thought - Prayogo, Agung; Harahap, Indra (Yayasan Salam Cerdas Al-Fattah, 2023)
This paper specifically examines Ibn Khaldun's political thought which is the basis of religious and state values. In this paper, the values of Ibn Khaldun's thought are raised, starting from tracing the historical aspects and socio-political conditions in his life journey and conducting a review by doing keywords relevant to the title that the author has set. This type of research is qualitative with the Library Reasearch method, data sources are obtained through the literature of journal articles, books, theses, the internet, and the web related to the object to be studied, the data is analyzed with the stages of data reduction, data analysis and conclusion drawing to obtain accurate and objective information. Based on the above, the findings in this paper are that the figure of Ibn Khaldun provides colors and lessons through his works and in his life journey in every aspect of the sector such as, state, social, economic, cultural and education which has always been a reference and study of Muslim intellectuals. The values that can be taken in the study of Ibn Khaldun's character can be concluded, namely the value of leadership, religion and state, economy and socio-culture.